Perlindungan Anak Dalam Mengonsumsi Obat Sirup Yang Menimbulkan Gagal Ginjal Akut - Abdul Cholid; Syafrida Syafrida; Warsito Warsito (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The Food and Drug Monitoring Agency (BPOM) as a non-ministerial government institution in carrying out its role and function supervises the distribution of drugs and food circulating in the community. BPOM's supervisory function is carried out before and after the product is circulated in the community. In the case of liquid syrup drugs cause acute kidney failure in children in a short time which causes death in children. The problem is, what are the roles and responsibilities of BPOM in overseeing the production of children's liquid medicines causing acute kidney failure, and how are consumers' protection for children due to consuming children's liquid medicines causing acute kidney failure? The research method, library research used is in the form of secondary data consisting of primary legal materials, secondary legal materials, and tertiary materials. The research is normative juridical in nature and data analysis is carried out qualitatively. Research result. BPOM's role in carrying out the supervisory function is to increase the distribution of drugs before they are circulated or after they are circulated in the community. Legal protection for child consumers as a result of consuming syrup drugs that cause acute kidney failure is that business actors producing syrup drugs provide reimbursement for hospital treatment costs, provide compensation if they cause death, criminal proceedings for using dangerous substances are at the threshold, and state administrative legal sanctions in the form of written warnings, fines, freezing business temporarily, revoking permits for completion and withdrawing drug solutions from circulation.Keywords: Legal Protection; Child Consumers; Acute Kidney Failure AbstrakBadan Pengawasan Obat dan Makanan (BPOM) sebagai lembaga pemerintah non Kementerian dalam melaksanakan peran dan fungsinya melakukan pengawasan terhadap peredaran obat dan makanan yang beredar di masyarakat. Fungsi pengawasan BPOM dilakukan sebelum dan setelah produk beredar di masyarakat, namun muncul kasus obat sirup menimbulkan gagal ginjal akut yang mematikan pada anak. Permasalahan, bagaimana peran dan tanggung Jawab BPOM dalam mengawasi produksi obat cair anak menimbulkan gagal ginjal akut, dan bagaimana perlindungan konsumen terhadap anak akibat mengkonsumsi obat cair anak menimbulkan gagal ginjal akut. Metode penulis mengunakan penelitian kepustakaan bersifat yuridis normatif dan analisa data dilakukan secara kualitatif. Hasil penelitian. Peran BPOM dalam melaksanakan fungsi pengawasan untuk meningkatkan pengawasan peredaran obat sebelum beredar maupun setelah beredar di masyarakat. Perlindungan hukum konsumen anak akibat mengonsumsi obat sirup menyebabkan gagal ginjal akut adalah pelaku usaha memproduksi obat sirup memberi penggantian biaya pengobatan rumah sakit, memberi santunan jika menimbulkan kematian, diproses pidana karena mengunakan bahan- bahan berbahaya diambang batas dan sanksi hukum admintrasi negara berupa peringatan tertulis , denda, membekukan usaha sementara, mencabut izin usahanya dan menarik obat sirup dari peredaran.Kata Kunci: Perlindungan Hukum; Konsumen Anak; Gagal Ginjal Akut